Financial Administration and Budgeting Planning on the Realization of Budget Absorption - Hikmat (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
This study was conducted to analyze the influence of financial planning and administration on the realization of budget absorption at the Tangerang City Education and Culture Office. The research uses a descriptive method with a quantitative approach. Data were collected using questionnaires, observations, and cumentated studies. The data analysis technique uses a multiple linear regression model with the help of the SPSS program. The results of the study show that financial planning and administration have a significant effect on the realization of budget absorption and financial administration causes an increase in the realization of budget absorption. From the test of the determination coefficient, financial planning and administration contribute to the realization of budget absorption. Keywords: Planning, Financial Administration, Realization of Budget Absorption.